Building an electrochemical series of metals in pyrrolidinium-based ionic liquids. Issue 40 (24th June 2020) - Jung, Yeojin; Dilasari, Bonita; Bae, Wi-Sup; Kim, Hong-In; Kwon, Kyungjung
Abstract : An electrochemical series of pyrrolidinium-based ionic liquids is established by designing a redox system where only one kind of anion is present in the electrolyte and metal ions are supplied by anodic dissolution. Abstract : An electrochemical series of pyrrolidinium-based ionic liquids is established by designing a redox system where only one kind of anion is present in the electrolyte and metal ions are supplied by anodic dissolution. This is the first report where an electrochemical series is established in pure ionic liquids.